The Aplication of Concrete Learning Media to the Development of Communication in Children with Hearning Impairments at PAUD Biru Bangsa - Indah Mulyana; Septiyani Endang Yunitasari; Melva Evalin Tobing; Nurlaelah; Endah Rachmawati; Ni Nyoman Emi Herawati (Universitas Panca Sakti Bekasi, 2023)
In the developmental phase, not all individuals experience development according totheir stages, children who experience developmental obstacles are categorized as children with special needs, children with special needs with hearing impairments have difficulties that focus on communication and language due to hearing barriersas well as delays in speech. Hearing barriers, especially related to communication, greatly affect the level of development of children in the social-emotional field. Children with hearing impairments have a direct impact on the development of receptive and expressive communication. So that it requires proper handling in orderto maximize the child's ability comprehensively. The purpose of this study was to determine the description and effect of the application of concrete media on the communication development of students with hearing impairments. data collectionin this study using observation and interview techniques. The results of this study found that the application of concrete media can attract the attention of children withhearing impairments, help children understand words, so that two-way communication can be established. The application of concrete media has an influence on the development of communication of children with hearing impairments